1990
DOI: 10.1902/jop.1990.61.8.475
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Characterization of Root Surface‐Associated Microbial Plaque in Localized Juvenile Periodontitis

Abstract: The purpose of this investigation was to characterize by scanning electron microscopy, the microbial morphotypes associated with the roots of teeth from patients exhibiting localized juvenile periodontitis (LJP). Eighteen teeth were examined from 10 adolescent patients who satisfied the standard clinical diagnostic criteria for LJP. The microscopic evaluation was facilitated by dividing that portion of the root exposed to the periodontal pocket into coronal, middle, and apical one‐thirds. Controls consisted of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…An additional 15 articles were not retained due to lack of specific microbiological data regarding the parameters tested in this review: two papers reported data on bacterial morphotypes only (Liljenberg & Lindhe 1980, Douglass et al 1990), two were on E. corrodens (Chen et al 1989, Chen & Ashimoto 1996), and two on Peptostreptococcus micros (Rams et al 1992a, Turng et al 1996). One single article dealt with sulphate‐reducing bacteria (Langendijk et al 2000), Capnocytophaga sp.…”
Section: Resultsmentioning
confidence: 99%
“…An additional 15 articles were not retained due to lack of specific microbiological data regarding the parameters tested in this review: two papers reported data on bacterial morphotypes only (Liljenberg & Lindhe 1980, Douglass et al 1990), two were on E. corrodens (Chen et al 1989, Chen & Ashimoto 1996), and two on Peptostreptococcus micros (Rams et al 1992a, Turng et al 1996). One single article dealt with sulphate‐reducing bacteria (Langendijk et al 2000), Capnocytophaga sp.…”
Section: Resultsmentioning
confidence: 99%
“…The application of the latest molecular techniques in this area should advance our understanding of the role of these organisms. However, using predominantly microscopic techniques, a number of investigations suggest their involvement in localized early-onset periodontitis (8,24,35,44,88,106,142,185) (Table 1).…”
Section: Spirochetesmentioning
confidence: 99%
“…1 Until the publication of the Crespo et al paper, 2 in which the presence of transient external resorptions on the radicular surfaces of teeth with adult periodontitis (current terminology: chronic periodontitis 3 ) was verified, there were very few references to resorptions in periodontally diseased teeth. [4][5][6][7][8] Only two studies 2,5 classified teeth according to the severity of periodontitis. These studies observed that the more severe the periodontitis, the greater the number of transient external resorptions.…”
mentioning
confidence: 99%